Mapping knowledge domain of acupuncture for Parkinson’s disease: a bibliometric and visual analysis - Zhao, Yanqing; Huang, Li; Li, Wentao (Frontiers in Aging Neuroscience, 2024)
Objective: This study points to probing the inclination and mapping knowledge domain of acupuncture for Parkinson's disease through bibliometrics. Methods: Papers published to date with respect to acupuncture for Parkinson's disease were searched from Web of Science on February 1, 2024. The output of scientific research, country, organization, author/cited author, keyword, journals and cited reference of the researches were dissected utilizing the efficacious bibliometric information. Using VOSviewer software,CiteSpace, GraphPad Prism, and Scimago Graphica, the acupuncture for Parkinson's disease studies was visualized as a network map in conformity to the publication year. Results: The cumulative publication trend is increasing year by year. China is the most productive country. Close cooperation between countries is mainly distributed in Europe. Institutional collaboration is limited chiefly to Chinese universities of traditional Chinese medicine. Park HJ is the most productive author, "Movement Disorders" journal has the most publications, and the most crucial journal is "Brain Research," which is mainly based on neuroscience professional journals. Kim SN is the most cited author, Eisenberg DM is a hot author in this field, mouse model, systematic review, and nonmotor symptoms are high-frequency research, and messenger RNA of substantia nigra is a hot 2 keyword in this field. Choi YG's 2009 paper, published in the Neuroscience Letters journal, is a critical reference. The main contents of the hot papers are Eisenberg DM (1998), randomized trials of acupuncture for non-motor symptoms of PD, and research on the neuroinflammatory regulatory mechanism of acupuncture for PD. Conclusion: The bibliometric analysis offers a exhaustive generality of the advancement and worldwide trends in acupuncture treatments for Parkinson's disease, shedding light on potential avenues for prospective research.